Laboratory evaluation of synthetic blends of L-(+)-lactic acid, ammonia, and ketones as potential attractants for aedes aegypti - Venkatesh, P. M.; Sen, A. (Journal of the American Mosquito Control Association, 2017)
Attraction of Aedes aegypti to various binary, trinary, and quaternary blends of lactic acid and ketones with or without ammonia was studied using a dual choice olfactometer. A dose dependent attraction was observed in cases of single compounds where cyclopentanone attracted the highest percentage (36.9 +/- 1.8%) of Ae. aegypti when tested alone. No significant difference was observed between the attraction levels of trinary and binary blends of lactic acid and acetone or butanone when tested against clear air. However, in competitive bioassays, the trinary blend of lactic acid, acetone, and butanone was significantly preferred over binary blends of individual compounds (P < 0.05). Acetylacetone was weakly attractive when tested alone but showed additive attraction when blended with lactic acid. However, acetylacetone acted as an attraction inhibitor when blended with other compounds. Cyclopentanone was attractive, but enhancement of attraction was not observed when blended with other components. Addition of ammonia to binary or trinary blends of lactic acid, acetone, and/or butanone did not increase the attraction significantly. In competitive bioassays, the blends containing ammonia were significantly preferred over the blends lacking ammonia (P < 0.05). This highlights ammonia as an essential component of synthetic blends. A quaternary blend of lactic acid, ammonia, acetone, and butanone was most attractive (65 +/- 1.5%) and preferred blend of all other combinations.